EVALUATION OF THE IMPLEMENTATION OF SHIPPING TRAINING POLICY AT THE BAROMBONG SHIPPING POLYTECHNIC - Abdul Mushawwir; Muhlis Madani; Nuryanti Mustari (SOSIOEDUKASI, 2026)
Introduction: This paper examines the implementation of maritime training policies at Politeknik Pelayaran Barombong, a maritime vocational school in Makassar, Indonesia. The maritime sector is crucial for Indonesia, an archipelagic nation relying heavily on sea transportation for logistics, infrastructure, and industry. This study investigates how the institution’s training programs align with international standards and their effectiveness in preparing skilled seafarers. The research questions are: How is the maritime training policy implemented at Politeknik Pelayaran Barombong? What are the outcomes in terms of graduate competency and industry absorption? Novelty: This research fills a gap by analyzing maritime training policies at a specific Indonesian institution, focusing on the direct impact on industry employment, a topic not widely explored in previous studies. Methods: A qualitative descriptive approach was used, employing interviews, direct observations, and documentation to gather data from key informants at Politeknik Pelayaran Barombong, including instructors and maritime experts. Results: The study finds that Politeknik Pelayaran Barombong has successfully implemented maritime training policies, ensuring adequate infrastructure and adherence to international standards like STCW. However, challenges remain, particularly in achieving optimal graduation rates for participants with lower educational backgrounds. Despite this, 85% of graduates are absorbed by the maritime industry within six months. Conclusion: While the implementation of maritime training policies has been successful, improvements are needed to enhance graduation rates and address challenges faced by students. Expanding the focus to include external industry stakeholders could help bridge gaps between academic curricula and industry needs.